Legal and Constitutional Protection Of the Basic Rights and Freedoms- in the Basic Palestinian Law - Shalaldeh, Muhammad Al-; Abu Ja'far, Ahmad Hasan (revue mofakir, 2018)
يعتبر الدستور في معظم دول العالم الضمانة الأساسية للحقوق والحريات، و يتولى الدستور أيضا الموازنة بين حقوق وحريات الناس، والمصلحة العامة للدولة . تتمثل مشكلة البحث في عدم وجود رقابة فعالة وحقيقية من قبل المجلس التشريعي الفلسطيني من أجل ضمان حقوق الإنسان والحريات في فلسطين .      تنقسم هذه الدراسة إلى فصلين : يتناول الفصل الأول تطور حقوق الإنسان دوليا وإقليميا، تعريفها وموقعها في القانون الأساسي في فلسطين . ويتناول الفصل الثاني الضمانات الأساسية للفلسطينيين لحقوق وحريات الفلسطينيين المذكورة في القانون الفلسطيني الأساسي .       خلصت الدراسة إلى بعض التوصيات : إن دولة فلسطين تبذل قصارى جهدها لتعزيز وحماية حقوق الإنسان ، وعلى دولة فلسطين تعديل التشريعات المحلية الخاصة بها من أجل مواكبة الاتفاقيات الإقليمية والدولية التي تحمي حقوق الإنسان، وعلى رأسها حق الشعب الفلسطيني في تقرير المصير . ومن الضرورة بمكان حماية وتعزيز حقوق الإنسان في فلسطين من خلال تفعيل الدور الرئيسي للمحكمة الدستورية والتي أنشئت حديثا، وهذا يدعو إلى المراقبة الدستورية على شرعية القوانين التي تشكل ضمانة للحقوق والحريات ل لشعب الفلسطيني .   Abstract Constitution in most of the world countries is considered the main guarantee for the rights and freedoms. Constitution also balances between the rights and freedoms of people, and public interest of the state . The research problem of this study appears in the absence of an effective and real control by the Palestinian Legislative Council in order to guarantee human rights and freedoms in Palestine. This study is divided into two chapters. The first deals with the evolution of human rights internationally and regionally, defining it and its location in the Basic Law in Palestine. The second chapter deals with the basic guarantees for the Palestinians mentioned in the Basic Palestinian Law. The study concluded to some recommendations: The Palestine State should do its best to promote and protect human rights. The Palestine State has to change its local legislations in order to keep up with the regional and international conventions that protect human rights, primarily the right to self-determination of the Palestinian people. It is also essential to protect and promote human rights in Palestine through activating the main role of the Constitutional Court which has been founded recently, and this calls for constitutional control on the legitimacy of laws, which constitute a guarantee of the rights and freedoms for the Palestine people.